2016
DOI: 10.1002/elps.201600091
|View full text |Cite
|
Sign up to set email alerts
|

Diffusiophoretic mobility of charge‐regulating porous particles

Abstract: The diffusiophoresis of a charge-regulating porous sphere, such as polyelectrolyte coil, with an arbitrary thickness of the electric double layer in an electrolyte solution prescribed with a concentration gradient is analytically studied for the first time. The ionogenic functional groups and hydrodynamic frictional segments distribute uniformly within the permeable particle, and a charge regulation model for the association and dissociation reactions of the functional groups relates the fixed charge density t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Several derivations exist for both electrolytic and non-electrolytic solutes. Recent work in the area focuses on diffusiophoresis in concentrated electrolytes (Prieve et al, 2019), multiple electrolytes (Chiang and Velegol, 2014;Gupta et al, 2019), dependence of mobility on solute concentration (Gupta et al, 2020;Lee et al, 2023b), multivalent electrolytes (Wilson et al, 2020), particle shape (Doan et al, 2023) and composite particles (Li and Keh, 2016;Mondal et al, 2023).…”
Section: Passive Diffusiophoresis: a Colloidal Focusing Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Several derivations exist for both electrolytic and non-electrolytic solutes. Recent work in the area focuses on diffusiophoresis in concentrated electrolytes (Prieve et al, 2019), multiple electrolytes (Chiang and Velegol, 2014;Gupta et al, 2019), dependence of mobility on solute concentration (Gupta et al, 2020;Lee et al, 2023b), multivalent electrolytes (Wilson et al, 2020), particle shape (Doan et al, 2023) and composite particles (Li and Keh, 2016;Mondal et al, 2023).…”
Section: Passive Diffusiophoresis: a Colloidal Focusing Mechanismmentioning
confidence: 99%
“…Several derivations exist for both electrolytic and non-electrolytic solutes. Recent work in the area focuses on diffusiophoresis in concentrated electrolytes(Prieve et al, 2019), multiple electrolytes(Chiang and Velegol, 2014;Gupta et al, 2019), dependence of mobility on solute concentration(Gupta et al, 2020;Lee et al, 2023b), multivalent electrolytes(Wilson et al, 2020), particle shape(Doan et al, 2023) and composite particles(Li and Keh, 2016;Mondal et al, 2023).Observation in experiments: The most striking feature of passive diffusiophoresis is the "focusing" effect where a region of high colloid concentration is observed. This, in effect, is as if diffusiophoresis imparts a "negative diffusion" coefficient to colloids(Murray, 2003).…”
mentioning
confidence: 99%
“…Diffusiophoresis of a charged particle under macroscopic electrolyte concentration gradients interacting with the electric double layer encompassing the particle, accompanied by the relative diffusioosmotic flow of the ambient fluid, is a well–known electrokinetic phenomenon applied to solid–liquid separations . In an unbounded solution of a symmetric electrolyte with a uniform concentration gradient n, the diffusiophoretic velocity of a particle is as follows : 0trueboldUfalse(0false)=εζηkTZenn0()α+prefixlnprefixcoshtrueζ¯ζ¯,where 0truetrueζ¯=Zeζ4kT,0trueα=D¯2D¯1D¯2+D¯1,η and ε are the viscosity and dielectric permittivity, respectively, of the fluid, ζ is the zeta potential of the particle surface, Z is the valence of the symmetric electrolyte, D¯1 and D¯2 are the diffusivities of the anion and cation, respectively, n0 is the prescribed electrolyte concentration at the particle center, e is the elementary electric charge, k is the Boltzmann constant, and T is the absolute temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusiophoresis of a charged particle under macroscopic electrolyte concentration gradients interacting with the electric double layer encompassing the particle, accompanied by the relative diffusioosmotic flow of the ambient fluid, is a well-known electrokinetic phenomenon applied to solidliquid separations [1,2]. In an unbounded solution of a symmetric electrolyte with a uniform concentration gradient ∇n ∞ , the diffusiophoretic velocity of a particle is as follows [3]:…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated that the diffusion of 45‐nm nanoparticles in 300 nm pores can be satisfactorily explained by hydrodynamic frictions . Along these lines, the diffusiophoresis of a charge‐regulating porous sphere is analytically described for the first time by Keh's group . Specifically, the electrokinetic equations governing the electric potential, ionic electrochemical potential, and fluid velocity distributions were solved as power‐series expansions in the basic fixed charge density and highlighted the differences between these particles and those with impermeable properties.…”
mentioning
confidence: 99%